Menerapkan Jiwa Entrepeneur Melalui Kegiatan Market Day Bagi Siswa Di UPT SD Negeri 206 Gresik - Nadyah Amelia Putri; Ni Made Ida Pratiwi (Pusat Riset dan Inovasi Nasional, 2023)
This study explores the implementation of entrepreneurial values through Market Day activities at UPT SD Negeri 206 Gresik, focusing on fifth-grade students. A dynamic economy and increasing competition demand education that not only develops cognitive intelligence but also skills and creativity. This research attempts to provide a solution by applying entrepreneurial concepts through Market Day activities. The research targets fifth-grade students at UPT SD Negeri 206 Gresik, aiming to guide them towards positive endeavors. The study involves observation, interviews, and program socialization to provide an understanding of entrepreneurial values. This method encompasses planning, execution, and evaluation processes, encouraging students to develop creativity, communication skills, independence, and discipline. The results show that Market Day activities successfully build entrepreneurial character among students. Despite facing challenges such as a lack of student participation and limited space, these shortcomings are identified as opportunities for improvement in the future. It is hoped that the implementation of entrepreneurial values through practical activities like Market Day can help address unemployment challenges in Indonesia by shaping students ready to become job creators.